Problems and Peculiarities of the Light Industry Development in Ukraine: A Statistical Comparison with EU Countries - Ishchuk, S. O.; Sozanskyy, L. Yo. (Statistics of Ukraine, 2020)
The light industry is one of the basic strategic segments of the national economy, providing for 5.0% of budget revenues and 2.6% of Ukrainian merchandise exports, and, therefore, has a considerable potential for further development. The purpose of the article is to identify problems and peculiarities of the light industry development in Ukraine on the basis of a statistical comparison with EU countries. According to the research results, the systemic negative dynamics of the light industry output resulted in a lag between Ukraine and EU countries, e. g. 6 times from Poland, 21 times from Germany, and 73 times from Italy. The light industry in Ukraine (like in the leading EU countries) specializes in manufacturing of final consumption products, which share in the output is more than 60%. However, despite such specialization, nearly 90% of the domestic demand for the light industry goods is met by imports. At the same time, the significant export orientation of textile and other light industry industries given that all the production and consumption segments of these industries in Ukraine have a strong import dependence indicates a high share of tolling operations in the Ukrainian exports. The development of the Ukrainian light industry is hampered by the following key problems: high dependence on imported raw materials, supplies and components; low price competitiveness of home-made goods on the domestic market; the reliance of a large part of domestic companies in the industry on consumer-supplied raw materials. Hence, the priority of the government’s industrial policy for the light industry development is to restore (and further increase) raw materials supplies for textile and other domestic industries. The second objective is to create competitive conditions on the domestic market for the light industry by eliminating the shadow turnover in this segment. The third objective is to reduce the commodity exports, along with increasing exports of high quality products with a high share of value added.